Will rogers: native american cowboy, philosopher, and presidential advisor - Vásconez Narváez, María Lorena
This senior thesis, Will Rogers: Native American Cowboy, Philosopher, and Presidential Advisor, presents the story of Will Rogers, indicating especially the different facets of his life that contributed to his becoming a legend and a tribute to the American culture. Will Rogers is known mostly as one of the greatest American humorist of his time and, in fact, of all times. This work focuses on the specific events and experiences that drove him to break into show business, Hollywood, and the Press. It also focuses on the philosophy of Will Rogers as well as his best known sayings and oft-repeated quotations. His philosophy, his wit, and his mirth made him an important and influential part of everyday life in the society of the United States in his day and for years thereafter. This project is presented in four parts. First, I discuss Rogers? childhood and his life as a child-cowboy. Second, I detail how he became a show business star and a popular actor. Third, I recall his famous quotations and one-liners that are well known nowadays. Finally, there is a complete description of the honors and tributes that he received, and the places that bear Will Rogers name. Reading, writing, and talking about Will Rogers, the author of the phrase I never met a man I didn?t like, is to tell about a life-story of completeness and self-revelation, because he was a great spirit, a great writer, and a great human being.